Dictionary of Pharmaceutical Medicine - Nahler, Gerhard; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2013)
This dictionary includes various terms typically used in pharmaceutical medicine. The 3rd edition underlines the increasing importance of this science and the changing regulatory environment, especially focusing on the research and development of new therapies as well as on conducting clinical trials, marketing authorizations for new medicinal products, and safety aspects including pharmacovigilance. The number of keywords has been considerably enlarged and is accompanied by an up to date list of the most important websites. Similar to the previous editions, this new book explains roughly 1,000 abbreviations most commonly used in pharmaceutical medicine. This volume will be a valuable tool for professionals working in the pharmaceutical industry, medical and preclinical research, regulatory affairs, marketing and marketing authorization of pharmaceuticals.
Dictionary of pharmaceutical medicine -- Abbreviations/acronyms -- Selected bibliography -- Useful websites.
Keywords: Medicine; Pharmaceutical technology; Pharmacy; Biomedicine; Pharmaceutical Sciences/Technology.; Pharmacy